Synergistical action of the β2 adrenoceptor and fatty acid binding protein 2 polymorphisms on the loss of glomerular filtration rate in Chinese patients with type 2 diabetic nephropathy - Wang, Tao; Zhang, Yan; Wang, Ning; Liu, Qiong; Wang, ZeKai; Liu, Bing; Niu, Kai (International urology and nephrology, 2018)
Purpose Since altered sympathetic nerve activity and insulin resistance are implicated in the pathogenesis of type 2 diabetic nephropathy, we investigated the effect of polymorphic Arg16Gly and Gln27Glu in the β2 adrenoceptor gene and Ala54Thr in the fatty acid binding protein 2 gene on the estimated glomerular filtration rate (eGFR) in Chinese patients with the above disease. Methods A total of 552 diabetic subjects recruited from annual health examinations were studied. The eGFR was calculated from the Modification of Diet in Renal Disease equation for the Chinese. Plasma norepinephrine level and genotype were determined by high-performance liquid chromatography–tandem mass spectrometry and TaqMan method, respectively. Holter-derived heart rate viability (HRV) and the MRI-generated renal apparent diffusion coefficient (ADC) were evaluated. Results The Gly16Gly and Thr54Thr homozygotes had significantly higher microalbuminuria and lower eGFR against other genotypes in their individual polymorphism. Besides, the Gly16Gly variant exhibited markedly elevated norepinephrine level, whereas indicative of insulin resistance was increased in the Thr54Thr one. Multiple linear regression analysis further confirmed the independent genetic effect on the eGFR. Moreover, multifactor dimensionality reduction method detected a gene–gene synergistic action that subjects with the Gly16Gly/Thr54Thr genotype were exposed to higher risk of eGFR loss. Finally, these findings were accompanied by lower HRV and ADC, indicating sympathetically mediated hemodynamic changes. Conclusions By uncovering the genetic component of the coherent interplay between the elevated sympathetic nerve activity and metabolic disorders, our observations might promote the development of novel personalized prevention and management strategies against the diabetic nephropathy, especially in the genetically susceptible individuals.